2009
DOI: 10.1038/sj.bjc.6604969
|View full text |Cite
|
Sign up to set email alerts
|

Combination of adenoviral virotherapy and temozolomide chemotherapy eradicates malignant glioma through autophagic and apoptotic cell death in vivo

Abstract: Conditionally replicative adenoviruses (CRAds) represent a novel treatment strategy for malignant glioma. Recent studies suggest that the cytopathic effect elicited by these vectors is mediated through autophagy, a form of programmed cell death. Likewise, temozolomide (TMZ), a chemotherapeutic agent used for the treatment of malignant gliomas, also triggers autophagic cell death. In this study, we examined the potential to combine the two treatments in the setting of experimental glioma. In vitro, pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 43 publications
(55 reference statements)
1
50
0
Order By: Relevance
“…34 Activation of TRAIL receptor 2 by a human Cancer targeting Gene-Viro-Therapy of hepatoma X Cao et al single-chain fragment variable antibody HW1 can induce autophagic cell death in both TRAIL-sensitive and -resistant cancer cells. 35 Although the concurrence of autophagic and apoptotic cell death was reported from a combination of adenoviral virotherapy and temozolomide chemotherapy in malignant glioma, 36 the results presented here are the first to show that these two distinct programmed cell death pathways can be simultaneously induced by a single geneviral agent in hepatoma.…”
Section: Discussionmentioning
confidence: 87%
“…34 Activation of TRAIL receptor 2 by a human Cancer targeting Gene-Viro-Therapy of hepatoma X Cao et al single-chain fragment variable antibody HW1 can induce autophagic cell death in both TRAIL-sensitive and -resistant cancer cells. 35 Although the concurrence of autophagic and apoptotic cell death was reported from a combination of adenoviral virotherapy and temozolomide chemotherapy in malignant glioma, 36 the results presented here are the first to show that these two distinct programmed cell death pathways can be simultaneously induced by a single geneviral agent in hepatoma.…”
Section: Discussionmentioning
confidence: 87%
“…One of the potential avenues to increasing adenovirus potency that remains understudied is the mechanism by which adenoviruses induce cell lysis. In this regard, we along with other groups have shown that adenovirus infection results in macroautophagy (here referred to as autophagy) (12,15,41). Although it has been suggested that this cellular process might be linked to adenovirus-induced cell lysis (17), the underlying mechanism is still largely unknown.…”
mentioning
confidence: 98%
“…Till now, multimodality treatments with surgery, radiation and chemotherapy have led to some improvement in prognosis for patients with GBM (2,3). However, the 5-year survival rate for patients with GBM remains less than 5% and the median survival time is approximately one year (4).…”
Section: Introductionmentioning
confidence: 99%